2017
DOI: 10.1016/j.engstruct.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Elastic behavior of Cross Laminated Timber and timber panels with regular gaps: Thick-plate modeling and experimental validation

Abstract: In the present paper, the influence of periodic gaps between lamellas of Cross Laminated Timber (CLT) on the panel's elastic behavior is analyzed by means of a periodic homogenization scheme for thick plates having periodic geometry. Both small gaps, due to the fabrication process of not-gluing lateral lamellas, and wider gaps are investigated. The results obtained with the periodic homogenization scheme are compared to existing closed-form solutions and available experimental data. It appears that the plate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…Following Hashin (1986Hashin ( , 1987 variational principles, Nairn (2017) also suggested an equivalent layer in-plane shear modulus. Finally, Franzoni et al (2017Franzoni et al ( , 2018 also studied this behavior at the scale of a CLT plate with small or large gaps by means of a periodic plate homogenization scheme and suggested closed-form formula.…”
Section: Influence Of Free Narrow Edgesmentioning
confidence: 99%
See 3 more Smart Citations
“…Following Hashin (1986Hashin ( , 1987 variational principles, Nairn (2017) also suggested an equivalent layer in-plane shear modulus. Finally, Franzoni et al (2017Franzoni et al ( , 2018 also studied this behavior at the scale of a CLT plate with small or large gaps by means of a periodic plate homogenization scheme and suggested closed-form formula.…”
Section: Influence Of Free Narrow Edgesmentioning
confidence: 99%
“…Finally, the detailed treatment of the cross layer shear stiffness G C Z requires also a 3D analysis as it involves complex interactions with the upper and lower longitudinal layers. Neglecting the influence of the sawing pattern, this analysis was achieved by Franzoni et al (2017Franzoni et al ( , 2018 and closed-form formula were suggested as well. This required a modeling based on a thick plate homogenization scheme (Lebée and Sab, 2012b;Sab and Lebée, 2015).…”
Section: Influence Of Free Narrow Edgesmentioning
confidence: 99%
See 2 more Smart Citations
“…• CLT3 is an aerated CLT with a similar configuration to CLT2 (80 − 40 − 40 − 40 − 80), but with 50% of voids in the three central layers. (This kind of configuration becomes indeed more and more popular in the last decade [24,25,26]. Similar local properties will be considered as CLT2 except for the rolling shear strength for which an equivalent strength of 2 is chosen because the contact between the central layer is ensured by one fourth ( 2 ) of the total surface, so that the maximum stress is four times the average evaluated by expression (13b).…”
Section: Influence Of the Shear Stiffness On The Buckling Loadmentioning
confidence: 99%